2020
DOI: 10.1002/capr.12288
|View full text |Cite
|
Sign up to set email alerts
|

Working with suicidal clients: Psychotherapists and allied professionals speak about their experiences

Abstract: Objective To ascertain the impact that working with suicidal clients has on health professionals. Design This research study used an online survey, which covered a broad range of questions in relation to the impact of working with suicidal clients. Method A total of 110 practitioners completed the online survey. The responses were analysed using descriptive statistics and thematic analysis. Results The findings highlighted how overwhelmed practitioners felt at the time of their client's death, expressing shock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Having patients with severe suicidal ideation was the most common professional adversity reported by psychiatrists and psychiatry trainees and conferred a higher risk for having an anxiety disorder in the latter. Dealing with patients who express suicidal intention seems to be the greatest difficulty psychiatrists can face in their profession [ 34 , 35 ]. It is a particularly difficult stressor to cope with [ 36 ], with reports of severe stress levels (comparable to the loss of a parent) in treating therapists, a substantial proportion of whom develop posttraumatic symptoms when a patient under their care commits suicide [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Having patients with severe suicidal ideation was the most common professional adversity reported by psychiatrists and psychiatry trainees and conferred a higher risk for having an anxiety disorder in the latter. Dealing with patients who express suicidal intention seems to be the greatest difficulty psychiatrists can face in their profession [ 34 , 35 ]. It is a particularly difficult stressor to cope with [ 36 ], with reports of severe stress levels (comparable to the loss of a parent) in treating therapists, a substantial proportion of whom develop posttraumatic symptoms when a patient under their care commits suicide [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a particularly difficult stressor to cope with [ 36 ], with reports of severe stress levels (comparable to the loss of a parent) in treating therapists, a substantial proportion of whom develop posttraumatic symptoms when a patient under their care commits suicide [ 37 ]. A sense of competence and confirmation of professional skills (when faced with this adversity) can only come from experience and training [ 35 ]. Accordingly, close supervision by a more experienced or attending psychiatrist working with established institutional protocols for providing additional resources to trainees to manage suicidal patients and reduce anxiety is required, together with help for them to deal with guilt and genuinely consider whether mistakes were made [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive aspects included using this experience to review and enhance their practice as well as a tendency to increase their self-care and provide support to colleagues with similar experiences ( n = 3). Mental health providers also reported that the aftermath of the event brought changes in their practice such as working longer hours, increased patient surveillance and note taking, and adjusting their work schedule (Scupham & Goss, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Saini et al (2016) reported that closer and longer relationships with clients were two important relational factors associated with increased distress. Witnessing the event and completion of suicide rather than incomplete suicide were further denoted by Scupham and Goss (2020) as factors relating to the event of suicidal behavior that further increased impact.…”
Section: Factors Increasing Vulnerabilitymentioning
confidence: 99%